The relationship between resilience and perceived practicum stress: the mediating role of self-efficacy - Ngui, Geok Kim; Lay, Yoon Fah (Penerbit UTM Press, 2017)
The purpose of this study is to determine the mediating role of three subdimensions of self-efficacy (instructional strategies, classroom management and students’ involvement) on the relationship between resilience and trainee teachers’ perceived practicum stress. Hypothesized multivariate model was tested using partial least square-structural equation modeling (PLS-SEM) with SmartPLS3.0 to determine the mediating effect self-efficacy on of these variables. The reflective measurement model analysis indicated a good statistical fit. The structural measurement model showed that resilience has a significant relationship with instructional strategies, classroom management and students’ involvement. The relationship between resilience and perceived practicum stress was also significant. However, the result showed that although classroom management was a significant mediator of the relationship between the studied variables, instructional strategies and students’ involvement were not. Hence, this implied that efficacy in classroom management enables trainee teachers to reduce perceived practicum stress more than efficacy in instructional strategies and students’ involvement